ANALYSIS OF TOURISM PERCEPTION USING THE IMPORTANCE PERFORMANCE ANALYSIS METHOD TOWARD JAYAGIRI HIKING TRAIL BANDUNG (International Journal of Psychosocial Rehabilitation, 2020)
The geographical location of Bandung which is surrounded by mountains has become an exotic tourist destination for local and foreign tourists. But a tour package offered to tourists who have an interest in hiking to explore the mountains of Bandung is relatively rare. Whereas the prospect of tourism in the form of ecotourism like that is quite a lot of devotees from both local and foreign tourists. In this case the Jayagiri Bandung hiking trail has not been maximally satisfying the desires of hiking tourists, it is necessary to analyze what influential factors are analyzed through Importance Performance Analysis (IPA). This analysis method is to find which elements are considered important by tourists, so that suggestions and conclusions can be drawn for the further development of Jayagiri hiking tours. This research produced an analysis that there are still many deficiencies that can reduce the experience of tourists in hiking trips, including hiking posts and adequate information boards, stalls to buy food, and the absence of public toilets. This needs special attention to be able to provide a good traveling experience and make tourists decide to repeat hiking again in Jayagiri, while from the gap analysis between satisfaction and interests it can be seen that the facilities or services of the Jayagiri hiking trail have not exceeded tourists' expectations.